London has fallen - Najafi, Babak, 1975-; Rothenberger, Creighton; Benedikt, Katrin; Gudegast, Christian; St. John, Chad.; Butler, Gerard, 1969-; Eckhart, Aaron; Freeman, Morgan; Aboutboul, Alon.; Bassett, Angela; Forster, Robert, 1942-; Haley, Jackie Earle, 1961-; et al. (Universal City, CA : Universal Studios, 2016)
After the British Prime Minister passes away under mysterious circumstances, his funeral is a must-attend event for leaders of the western world. However, what starts out as the most protected event on Earth turns into a deadly plot to kill the world's most powerful leaders, and unleash a terrifying vision of the future. Only three people have any hope of stopping it: the President of the United States, his formidable Secret Service head, and an English MI-6 agent who rightly trusts no one.
Sequel to: Olympus has fallen.
Gerard Butler, Aaron Eckhart, Morgan Freeman, Alon Moni Aboutboul, Angela Bassett, Robert Forster, Jackie Earle Haley, Melissa Leo.
DVD release of the 2016 motion picture.
Audience: MPAA rating: R; for strong violence and language throughout.
DVD ; anamorphic widescreen (2.40:1) presentation ; Dolby digital 5.1 surround (English and Spanish) and 2.0 stereo. (English DVS).
English; In English or dubbed Spanish, with optional subtitles in Spanish or French. English subtitles for the deaf and hard of hearing (SDH) Optional descriptive audio in English for the visually impaired.
Keywords: Prime ministers -- England -- Drama; Funeral rites and ceremonies -- Drama; Secret service -- United States -- Drama; Presidents -- United States -- Drama; Terrorists -- Drama; Feature films; Fiction films; Action and adventure films; Crime films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities